Electrostatic wave emission and diffusion of charged particles in plasmaspheric region - Prasad R.; Singh R.N. (My University, 2025)
Considering a mixture of cold and dense plasma of ionospheric origin and hot and tenuous plasma of plasmasheet origin, the emission of electrostatic spectrum is studied. Use is made of the test particle approach in computing the electric field power spectrum. The growth/damping rate of these electrostatic waves is studied. The diffusion coefficients of charged particles interacting resonantly with emitted electrostatic spectrum are computed. © 1989.